Assistance on Laboratory Activities in Primary Schools Oriented to a Saintific Approach for Creative Primary Teachers Tempel Sukorejo Bojonegoro - Prasetya, Agus; Asri, Wuwuh; Anjarwati, Ani (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
The training program focuses on improving the quality of science teachers in elementary school members of the MGMP science teachers. The aim is to improve teachers' skills in designing inquiry laboratory activities in the form of Student Worksheets (LKS) for science subjects. Inquiry-based worksheets in elementary schools need to be developed because they support teachers and students in science laboratory activities. Increasing teachers' abilities in planning and implementing science laboratory activities is very important because teachers have a very important role in the success of laboratory activities. By utilizing the use of inquiry-based learning with worksheets among teachers, it is hoped that it can have a positive impact on the quantity of science laboratory activities in elementary schools, foster a culture of teachers implementing an inquiry-based approach, and influence students to become skilled in science laboratory practice. This community service activity has been carried out in 3 stages, namely (1) Organizing inquiry modeling, (2) Designing inquiry laboratory activities and (3) Implementation of design results in simulation. The results obtained in real classes have a positive influence from students and teachers with the majority of students feeling guided and motivated by the existence of laboratory equipment that is tangible like the tools that are around